Analysis of Water Meter Accuracy in Pressure Variations and Flow Conditions in Gravimetry Test Equipment - Firmansyah, Dudi Adi (Universitas Padjadjaran, 2024)
A water meter is a device used to measure the volume of water used by customers and is used as a basis for determining water retribution. The influence of pressure both in the position before (upstream) and after the water meter (downstream), then flow conditions that could be temporal and stable also affect on the accuracy of the water meter. Then, in this study, a prototype of a water meter test equipment was made that was able to vary the pressure in two positions and flow conditions and then determine the error of the test water meter automatically from the weighing process. Prototype scales and sensors (pressure gauge sensors, flow gauge sensors and temperature gauge sensors) have accuracy and precision in the range of 93,4%-99,9% and were connected to smartphones via an Android app that has data acquisition capabilities. The test results showed three downward error trends, namely 6,63%-4,70% (Temporal Flow, Upstream Position Pressure Regulation); 4,41%-3,66% (Temporal Flow, Downstream Position Pressure Regulation) and 3,21%-1,76% (Temporal Flow, Downstream Position Pressure Regulation). The results of the analysis showed that the pressure difference between the upstream position and the downstream position that exceeded 0,63 bar caused the test water meter error to exceed the error limit of ±4%, especially in temporal flow conditions compared to stable flow.